Antibacterial efficacy of silver nanoparticles (AgNPs) against metallo-β-lactamase and extended spectrum β-lactamase producing clinically procured isolates of Pseudomonas aeruginosa - Maria Muddassir; Almas Raza; Sadaf Munir; Ahmad Basirat; Muddassir Ahmed; Mazia Shahid Butt; Omair Arshad Dar; Syed Shoaib Ahmed; Saba Shamim; Syed Zeeshan Haider Naqvi (Scientific Reports, 2022)
Abstract Resistance to carbapenems is a global threat, especially in developing countries with limited health resources. Prevalence, antibiogram, PCR detection of antibiotic resistance genes, and potency of Silver Nanoparticles (AgNPs) against multidrug-resistant (MDR) Pseudomonas aeruginosa were studied. Kirby-Bauer disc method and PCR were used to study antibiogram and drug resistance genes respectively in 255 isolates of Pseudomonas aeruginosa obtained from a tertiary care hospital. Silver nitrate (AgNO3) precursor salts were reacted with Aspergillus flavus culture filtrate to trigger the extracellular mycosynthesis of AgNPs. Mycosynthesis was first monitored regularly by visible ultraviolet spectroscopy that recorded AgNP peaks of approximately 400–470 nm. Confirmation by Transmission electron micrographs provided confirmation of AgNPs formed within a range of 5–30 nm. Individual and combined antibacterial activity of ten antibiotics and AgNPs was analyzed. Pearson correlation coefficients (r) were calculated for phenotypic and genotypic multidrug resistance. Data were evaluated using SPSS version 20. p-value < 0.05 was considered statistically significant. 61.5% were carbapenemase producers (p < 0.01). The recorded frequency of bla IMP-1, bla SHV, bla VIM, bla OXA, and bla TEM were 13%, 32%, 15%, 21%, and 43%, respectively. The reducing order of antimicrobial activity of antibiotics and AgNPs was piperacillin/tazobactam + AgNPs (31 mm), cefoxitin + AgNPs (30 mm) > amikacin + AgNPs (25 mm) > aztreonam + AgNPs (23 mm) > meropenem + AgNPs (22 mm) > imipenem + AgNPs (20 mm) > gentamycin + AgNPs (17 mm) > ciprofloxacin + AgNPs (16 mm) > cefoperazone/sulbactam + AgNPs (14 mm) ≥ ceftazidime + AgNPs (14 mm). The conjugated effect of AgNPs plus antibiotics showed a 0.15–3.51 (average of 2.09) fold-area augmentation of antimicrobial activity. AgNPs conjugated with antibiotics effectively inhibited MDR Pseudomonas aeruginosa. To the best of our understanding, this is an inaugural report from Punjab Pakistan enlisting co-expression of Metallo-β-lactamases, extended-spectrum β-lactamases, and AmpC-β-lactamase plus activity of antibiotic-AgNPs.